Adolescent development: From neurobiology to psychopathology. (December 2022) - Braams, Barbara R.; Krabbendam, Lydia
Abstract : Adolescence is a time of major psychological development in the cognitive, affective, and social domains. Development in these domains can also show interactions with each other. One way in which these interactions between these domains become apparent is in the form of risk-taking behavior in adolescence. Compared to children and adults, adolescents show increased risky decision-making. An example of risk-taking behavior is substance use, including smoking and the use of e-cigarettes (Huizink). A leading explanation for risk-taking behavior has been an increase in reward sensitivity in adolescence. However, adolescents also show differential processing of risk compared to children and adults. A focus on risk processing could broaden the perspective on adolescent risk-taking behavior (van Duijvenvoorde).